Proposta de retribuição por serviços da paisagem no geoparque Quarta Colônia (RS, Brasil): uma análise a partir dos serviços culturais em trilhas - Silva, Greice Kelly Perske da (2022)
In this thesis, ecosystem services are understood and discussed from the perspective of geographic science and, therefore, we chose to use the concept of landscape services, which are the benefits that human get from landscapes to maintain your well-being. Quarta Colônia Geopark is a territory where landscape services are considerably preserved, which is why it is a visiting itinerary for users who take trails, seeking an approximation with nature. Thus, the general objective was to propose, from the evaluation of the cultural services of the landscape offered by the trail activities in the Quarta Colônia Geopark, a system of payment for landscape services with a view to protecting the natural heritage and endogenous development of the territory. Among the specific objectives, we sought to map and assess the potential of cultural landscape services in the territory, in addition to understanding those involved in the offer (providers) and in the use of the trails (users), in order to discuss the institutional viability of a Retribution System for Cultural Services for trails in the Quarta Colônia Geopark. Around 40 kilometers of walking were carried out in nine field works to map and characterize the five study trails and to dialogue with the owners. The sample of trails was chosen from a panel of experts linked to hiking and tourism activities in rural properties in the Quarta Colônia Geopark. In order to understand the users of these trails, a questionnaire was applied to a total of 100 people during the hiking activities between September 2019 and March 2020. Most users of the trails in the Quarta Colônia Geopark are women with an average age of 34 years and domiciled outside the territory where the trails are located and maintain a very strong relationship with nature, mainly seeking health (physical and mental) when doing the trails. Finally, the aspects that could compose a policy model for the territory of the Quarta Colônia Geopark were identified, defining and presenting scope; scale and users; political and financial mechanism; reference levels; verification systems and degrees of participation in the construction of the remuneration system for landscape services in the research territory. It was therefore concluded that it is possible, pertinent and urgent to use cultural services to repay the providers of these services and mediators in the scope of the trails in the Quarta Colônia Geopark, aiming at the protection of this landscape. This retribution is not only a motivation for providers' environmental adaptation, but it goes beyond that, it is a way of transforming land use, migrating to uses that are more harmonious with the territory's landscape.